UK Standards for Microbiology Investigations : Detection of bacteria with carbapenem-hydrolysing β-lactamases (carbapenemases): Detection of bacteria with carbapenem-hydrolysing β-lactamases (carbapenemases). (2020) - Unknown
No abstract available